Pengaruh Leverage, Asset Growth, dan Kebijakan Dividen terhadap Kualitas Laba dengan Persistensi Laba sebagai Pemoderasi pada Sub Sektor Minyak, Gas, dan Batu Bara di Bursa Efek Indonesia - Bobby, Bobby; Tambun, Sihar (Media Akuntansi Perpajakan, 2025)
This research aims to examine the direct impact of leverage, asset growth, and dividend policy on earnings quality. The study also aims to investigate the moderating effect of earnings persistence on the influence of leverage, asset growth, and dividend policy on earnings quality in companies within the oil, gas, and coal sub-sector listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling method used is purposive sampling based on specific criteria. From the criteria set, a sample of 20 companies was obtained. The analysis method used includes selecting the best model, classical assumption tests (data quality tests), and hypothesis testing. The results of this study indicate that the dividend policy variable has a positive direct effect on earnings quality, and the moderating variable of earnings persistence strengthens the effect of dividend policy on earnings quality.